A rare case of recurrent adenoid cystic carcinoma of the breast with weak hormone receptor positivity - Jonathan W. Ray, MD; Mena Louis, DO; Nathaniel Grabill, MD; Jaime Morel Ruiz, MD; Priscilla Strom, MD (Radiology Case Reports)
Adenoid cystic carcinoma (ACC) of the breast is an exceptionally rare malignancy, accounting for less than 0.1% of all breast cancers. Despite its favorable prognosis, optimal management remains undefined due to its rarity and lack of consensus guidelines. We report a case of recurrent ACC of the breast, illustrating treatment challenges and the need for individualized management. A 64-year-old woman presented with a palpable mass in her left breast; imaging and biopsy confirmed ACC with very poor hormone receptor positivity. She started neoadjuvant chemotherapy but discontinued after 3 cycles due to severe neutropenia and lack of response. She then underwent breast-conserving surgery and radiotherapy. Three years later, she developed a local recurrence. Imaging and biopsy reconfirmed ACC and a subsequent total mastectomy achieved clear margins. Local recurrence of breast ACC can occur despite chemotherapy, surgery, and radiotherapy. Ineffectiveness of chemotherapy and recurrence after breast-conserving surgery suggest mastectomy might offer better local control. Hormone receptor positivity raises considerations for hormonal therapy, not standard for typically triple-negative ACC. The rarity of ACC complicates establishing standard protocols, necessitating personalized treatment plans based on tumor and patient factors. Recurrent breast ACC presents management challenges due to rarity and unpredictable behavior. More aggressive surgery and tailored treatment may improve outcomes. Further research is essential to develop evidence-based guidelines for managing this rare carcinoma.